ANALISIS PERAMALAN PERMINTAAN PRODUK PALET KAYU PADA CV BAROKAH UTAMA - simanjuntak, Veronika; Susanti, Elva (Computer Science and Industrial Engineering, 2022)
CV Barokah Utama is a company that produces wooden pallets with a variety of different sizes, namely the main product is wooden pallets with a size of 110 x 110 cm. CV Barokah Utama company needs to apply forecasting to predict the amount of demand that will occur in the coming period, while the avoid excess and shortage of production and raw materials. Forecasting is a structured calculation of historical data and current data for a certain period of time. So, in testing the forecasting data, various forecasting methods are carried out to get forecasting results with an accurate level that is close to the actual value and with the smallest error value. Forecasting methods used in this study are Moving Average, Weighted Moving Average and Holt's Double Exponential Smoothing. For the best forecasting results, there are the smallest MAD, MSE and MAPE values ​​as well as forecasting results that are close to the actual values. The right results after processing data from the three methods using the Holt's Double Exponential Smoothing method with the smallest error rate based on the MAD, MSE and MAPE values.